Editor’s Note. - Verdú, Elena (International Journal of Interactive Multimedia and Artificial Intelligence, 2025)
The International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI) is a diamond open access journal which provides an interdisciplinary forum in which scientists and professionals can share their research results and report new advances on artificial intelligence tools, theory, methodologies, systems, architectures integrating multiple technologies, problems including demonstrations of effectiveness, or tools that use AI with interactive multimedia techniques. The journal is supported by Universidad Internacional de La Rioja (UNIR) and by all those members of this multicultural community who, with a sense of commitment to the development of science, dedicate their knowledge and time to authoring, editing and reviewing tasks, and without whom this knowledge sharing project would not be possible. This regular issue begins with a series of five articles covering key advancements in the area of computing vision. In the following article, we move from the area of computer vision to another fast developing area, which is natural language processing (NLP). The following articles correspond to a monograph section on the Effects of Culture on Open Science and Artificial Intelligence in Education, compiled and edited by Tlili, Burgos and Kinshuk.